Prediction of Favorable Positions for Hydrocarbon Accumulation Controlled by Oil-Source Faults: A Case of Dazhangtuo Fault in the Qikou Sag, Bohai Bay Basin, East China - Jiang, Fei; Fu, Guang; Han, Guomeng; Dong, Xiongying; Zhang, Wei; Wang, Haoran; Hu, Xinlei (Frontiers in Earth Science, 2022)
Oil-source faults play an important role in controlling hydrocarbon accumulation, and traps near these faults are often the most favorable positions for hydrocarbon accumulation. However, not all nearby traps can accumulate oil and gas. Therefore, it is necessary to predict favorable positions of hydrocarbon accumulation controlled by oil-source faults. Based on the analysis of hydrocarbon accumulation patterns near oil-source faults, a new method coupling hydrocarbon transportation positions of oil-source faults and favorable traps to predict favorable hydrocarbon accumulation positions is proposed. In this method, the hydrocarbon transportation positions are identified by the paleo activity rate during the hydrocarbon accumulation period; the favorable traps are identified by superimposing the position of fault traps, the lateral sealing position of faults, and the distribution of sand bodies with the ability to store oil and gas. Finally, the sites of overlap between the hydrocarbon transportation positions and the favorable traps are regarded as favorable positions for hydrocarbon accumulation under the control of oil-source faults. This method is applied to predict the favorable positions of hydrocarbon accumulation in the Ban 2 oil group of the Shahejie Formation near the Dazhangtuo fault, in the Qikou Sag (Bohai Bay Basin, East China). The results show that the favorable positions of oil and gas accumulation along the Dazhangtuo fault in the Ban 2 oil group are mainly distributed in the northeast and center of the fault, and match well with the locations of the discovered oil and gas. Therefore, this method is useful to predict favorable hydrocarbon accumulation positions controlled by oil-source faults.